Study on thermal protective performance of thermal liner in a multi-layer clothing under radiant heat exposure. Issue 5 (June 2022) - Das, Tathagata; Das, Apurba; Alagirusamy, R
Different factors should be considered for designing fire protective clothing. Constructional parameters, air gap, and proper fibers selection are critical, which need to be investigated thoroughly. In this work, the effect of the number of layers of the thermal liner on the thermal protection properties of thermal protective clothing has been studied. An experiment has been conducted using the three-level three-factor Box-Behnken designing method; factors used are the number of layers of the thermal liner, the areal density of the thermal liner, and intensity of radiant heat flux. Analysis of Variance study has been performed to analyze the significance of the structural and test parameters and their interaction. Second-degree burn time or protection time has been observed to increase with the increase in the areal density of thermal liner and decrease with increased heat flux. As the number of layers increases, protection time also increases. The effect of the number of layers is more prominent at a lower level of heat flux than a higher level of heat flux.